Literatura e identidade cultural: uma perspectiva inglesiana no conto a feiticeira - DIAS, Vanessa Maia (2022)
Since literary art can be seen as the expression of society through language, the present work, nicknamed "Literature and cultural identity: an English perspective in the short story the sorceress" aims to address the Amazon and its cultural traits shown in the short story A witch. The methods adopted were of a bibliographic nature, as well as the reading of books, articles, magazines, and the production of records and summaries. To do so, we start with the collection Contos amazônicos, by the English author of Sousa. The theoretical foundation was essential to reach the results, and unravel the mysterious Amazon of myths, the caboclo and the Amazon woman. The theoretical basis of the research is given by Antonio Candido (1968-2006), Araripe Júnior (1963), Massaud Moisés (2006), Paes Loureiro (1995), among others.